Implementasi Media Evaluasi Pembelajaran Berbasis Game Wordwall Pada Mata Pelajaran Sejarah Kebudayaan Islam di MA Darul Ulum Palangka Raya - Anya Dani Kinasih; Asmawati Asmawati; Ayatusa'adah Ayatusa'adah (Kamaya: Jurnal Ilmu Agama, 2026)
The demands of 21st-century learning place learning evaluation not only as a tool for measuring learning outcomes but also as a means of increasing student engagement and motivation. In the subject of Islamic Cultural History (SKI), studies on the use of Wordwall as a game-based evaluation medium are still relatively limited, especially in the context of Islamic high schools. This study aims to describe the implementation of Wordwall as a medium for evaluating SKI learning and its impact on the engagement and learning motivation of 25 students in class XI at MA Darul Ulum Palangka Raya. This study uses a descriptive qualitative approach with observation, interview, and documentation techniques, as well as Miles and Huberman's data analysis model. The results show that Wordwall can increase students' cognitive and affective engagement, strengthen learning motivation, and facilitate teachers in conducting evaluations through automatic scoring and real-time feedback. The obstacles found include limited learning time and the readiness of devices and networks. The novelty of this study lies in the use of Wordwall as a game-based digital evaluation medium in SKI learning in madrasah aliyah, which functions not only as an assessment tool but also as an evaluation strategy that encourages active and meaningful learning.